2019
DOI: 10.1016/j.jcrc.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Transient acute kidney injury after major abdominal surgery increases chronic kidney disease risk and 1-year mortality

Abstract: Purpose:We conducted a retrospective cohort study to determine incidences of transient and persistent acute kidney injury (AKI) after major abdominal surgery and their impacts on long-term outcome. Materials and Methods:We enrolled 3,751 patients undergoing major abdominal surgery.Postoperative AKI was classified as transient or persistent based on the return of serum creatinine to the non-AKI range within 7 days post-surgery. Primary outcome was mortality within 1 year. We used multivariable Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…Mizota et al [38] reported that transient AKI was associated with higher risk for 1-year mortality and progression to CKD in a cohort of 3,751 patients submitted to general surgery. The incidence of transient AKI was 84%; however, this cohort defined transient AKI as renal recovery within 7 days post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Mizota et al [38] reported that transient AKI was associated with higher risk for 1-year mortality and progression to CKD in a cohort of 3,751 patients submitted to general surgery. The incidence of transient AKI was 84%; however, this cohort defined transient AKI as renal recovery within 7 days post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the prognostic impact of AKI duration using different diagnostic criteria as follows: transient azotemia (≤ 3 days) and acute tubular necrosis (≥ 4 days or needs renal replacement therapy [RRT]); [25] short (≤ 2 days), medium (3-6 days), and long (≥ 7 days or needs RRT) using the AKIN criteria; [6,26] T-AKI (≤ 7 days) and P-AKI (> 7 days) using the KDIGO criteria; [15,27] T-AKI (Scr ≤ 115 µmol/L at discharge) and P-AKI (Scr > 115 µmol/L at discharge) using the KDIGO criteria; [28] short (≤ 2 days), medium (3-5 days), and long (≥ 6 days) using the KDIGO criteria; [9] T-AKI (≤3 days) and P-AKI (> 3 days) using the AKIN criteria; [10] and short (≤ 2 days), medium (3-7 days), and long (> 7 days) using the KDIGO criteria; [7] In the present study, no independent associations were observed between T-AKI and poor outcomes. The discrepancies between these studies might reflect the substantial variety in the duration of recovery from AKI according to the various definitions of AKI, T-AKI, or P-AKI according to different study populations, patient ages, and etiologies of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Bould and colleagues 2 reported similar results with anaesthetic residents, who followed a senior colleague's instruction to give blood to a (simulated) Jehovah's Witness patient despite a clear documentation that this was against the wishes of the patient, a result confirmed in a subsequent study. 3 Not speaking up can have serious and even fatal consequences, and many bad outcomes could have been prevented if someone in the team had spoken up.…”
Section: The Physiology Of Oliguriamentioning
confidence: 99%
“…2 In a recent cohort study of intermediate-term outcomes, postoperative AKI was associated with an increased 1-yr mortality after major abdominal surgery. 3 These observational studies defined AKI according to the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines 4 : a documented 1.5-fold increase in baseline serum creatinine concentration within 7 days, or a 30 mmol L À1 increase in serum creatinine within 48 h, or a urine output of <0.5 ml kg À1 h À1 for DOI of original article: 10.1016/j.bja.2019.01.010.…”
mentioning
confidence: 99%